Current status of cytokine-induced killer cells and combination regimens in breast cancer - Jiang, Yuancong; Qiu, Jie; Ye, Nanwei; Xu, Yingchun (Frontiers in Immunology, 2025)
Breast cancer remains a significant health challenge worldwide, with substantial efforts aimed at understanding its pathogenesis, biological characteristics, and clinical triggers. Recently, immunotherapy such as the cytokine-induced killer cells combined with other drug therapies has offered new hope for patients with advanced breast cancer. However, the specific pathogenesis of combination regimens involving cytokine-induced killer cells remains elusive. Besides, the combination of immunotherapy with cytokine-induced killer cells might represent a novel breakthrough. This review outlines the current status of cytokine-induced killer cell therapies and their combination strategies, especially the combination of chemotherapy with molecularly targeted treatments, for the management of breast cancer.